2006
DOI: 10.1103/physrevb.73.104117
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of interface dynamics during the fcc-bcc transformation of a martensitic nature

Abstract: The structural and dynamic properties of the interface during the fcc-bcc transformation in pure iron have been investigated by molecular dynamics simulations. An embedded atom method potential was used for the atomic interactions. Two interfaces, close to the Bain and Kurdjumov-Sachs orientation relations, have been examined during the fcc-to-bcc transformation. In each simulation the system was left to evolve freely at the imposed temperature. In a system with fully periodic boundaries no interface motion ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 19 publications
(12 reference statements)
6
52
1
Order By: Relevance
“…For example, Sinclair and Hoagland 14) examined the role of fault band intersections in the nucleation of martensite from austenite using the EAM potential fit by Ackland et al. 15) Bos and coworkers 16) estimated the interface velocity during the fccto-bcc phase transformation in pure iron in the range of 200-700 m/s using the Johnson-Oh potential. 17) In addition, we have investigated the kinetics of the fcc-bcc heterointerface during the fcc-to-bcc phase transformation with respect to ORs ranging from Nishiyama-Wasserman (N-W) OR 18,19) to Kurdjumow-Sachs (K-S) OR 20) using the Finnis-Sinclair potential 21) and revealed that there are two different propagation behaviors of the heterointerface: a planar propagation for the heterointerface with the N-W or near N-W ORs and a fast needlelike growth after initial planar growth for the heterointerface with the K-S or near K-S ORs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sinclair and Hoagland 14) examined the role of fault band intersections in the nucleation of martensite from austenite using the EAM potential fit by Ackland et al. 15) Bos and coworkers 16) estimated the interface velocity during the fccto-bcc phase transformation in pure iron in the range of 200-700 m/s using the Johnson-Oh potential. 17) In addition, we have investigated the kinetics of the fcc-bcc heterointerface during the fcc-to-bcc phase transformation with respect to ORs ranging from Nishiyama-Wasserman (N-W) OR 18,19) to Kurdjumow-Sachs (K-S) OR 20) using the Finnis-Sinclair potential 21) and revealed that there are two different propagation behaviors of the heterointerface: a planar propagation for the heterointerface with the N-W or near N-W ORs and a fast needlelike growth after initial planar growth for the heterointerface with the K-S or near K-S ORs.…”
Section: Introductionmentioning
confidence: 99%
“…Sinclair and Hoagland 21) examined the role of fault band intersections in the nucleation of martensite from austenite by MD simulation with the EAM potential. Bos et al performed kinetic MC 22) and MD 23) simulations to discuss the kinetics during phase transformation of iron from the fcc to the bcc phase. Nagano and Enomoto 24) calculated the interfacial energy between fcc and bcc iron with various orientations by MC calculation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the interfaces explored so far in kinetic simulations are not typical of those observed in experiments. [98][99][100][101][102][103] Therefore, we only concern ourselves here with calculations of interfacial energy by atomistic simulations. Before summarising the simulation results, several key issues that have substantial effects on the results, and that have not been paid sufficient attention in the past, will be discussed.…”
Section: Interfacial Energy Interfacial Structure and Morphology By mentioning
confidence: 99%
“…As a result of rapid advances in computing techniques, atomistic simulations have become a powerful tool for obtaining fundamental knowledge of interfaces, 92 and numerous results have been obtained both on the thermodynamics 86,87,[93][94][95][96][97] and the kinetics [98][99][100][101][102][103] of interfaces. However, the interfaces explored so far in kinetic simulations are not typical of those observed in experiments.…”
Section: Interfacial Energy Interfacial Structure and Morphology By mentioning
confidence: 99%